Proceedings of the 15th ACM/IEEE-CS Joint Conference on Digital Libraries 2015
DOI: 10.1145/2756406.2756927
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Digital Libraries

Abstract: This tutorial is a thorough and deep introduction to the DL field, providing a firm foundation: covering key concepts and terminology, as well as services, systems, technologies, methods, standards, projects, issues, and practices. It introduces and builds upon a firm theoretical foundation (starting with the '5S' set of intuitive aspects: Streams, Structures, Spaces, Scenarios, Societies), giving careful definitions and explanations of all the key parts of a 'minimal digital library', and expanding from that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Comparatively studies in Korea and Taiwan reported that microalbuminuria; proteinuria and GFR levels contribute to diabetes prevalence [7][8][9]. Age, co6morbidities, smoking, and lower GFR also attributes to CKD [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively studies in Korea and Taiwan reported that microalbuminuria; proteinuria and GFR levels contribute to diabetes prevalence [7][8][9]. Age, co6morbidities, smoking, and lower GFR also attributes to CKD [10,11].…”
Section: Introductionmentioning
confidence: 99%